Children's health priorities and interventions. (14th September 2015) - Were, Wilson M; Daelmans, Bernadette; Bhutta, Zulfiqar; Duke, Trevor; Bahl, Rajiv; Boschi-Pinto, Cynthia; Young, Mark; Starbuck, Eric; Bhan, Maharaj K
Abstract : Wilson Were and colleagues explain why the global community should continue to invest in children's health, to complete the unfinished child survival agenda and tackle the emerging child health priorities